Effect of adenosine on the growth of human T-lymphocyte leukemia cell line MOLT-4 - Streitová, Denisa; Weiterová, Lenka; Hofer, Michal; Holá, Jirina; Horváth, Viktor; Kozubík, Alois; Znojil, Vladimír (Cancer investigation, 2007)
Adenosine has been observed to suppress the growth of MOLT-4 human leukemia cells in vitro. Changes in the cell cycle, especially increased percentage of cells in S phase, prolonged generation time, and induction of apoptosis at higher adenosine concentrations have been found to be responsible for the growth suppression. Dipyridamole, a drug inhibiting the cellular uptake of adenosine, reversed partially but significantly the adenosine-induced growth suppression. It follows from these results that the action of adenosine on the MOLT-4 cells comprises its cellular uptake and intracellular operation. These findings present new data on anticancer efficacy of adenosine.
Keywords: biologický transport; nádorové buněčné linie; apoptóza; inhibitory fosfodiesteras; Biological Transport; Leukemia, T-Cell; Phosphodiesterase Inhibitors; adenosin; Cell Line, Tumor; Cell Proliferation; Antineoplastic Agents; protinádorové látky; Adenosine; Humans; Dipyridamole; proliferace buněk; dipyridamol; leukemie T-buněčná; lidé; Apoptosis